2021
DOI: 10.1094/phyto-09-20-0405-r
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Genetic Population Structure of Cryphonectria parasitica and Its Associated Hypovirus Across an Invasive Range of Chestnut Blight in Europe

Abstract: Chestnut blight has spread throughout Europe since the introduction of its causal agent Cryphonectria parasitica over 70 years ago. In our study, we have analysed diversity of vegetative compatibility (vc) and microsatellite genotypes of C. parasitica, as well as sequence diversity of Cryphonectria hypovirus 1 (CHV1) in six populations from Switzerland, Croatia and North Macedonia. Resampling of local populations that were already investigated more than a decade ago allowed us to analyse the spatial and tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 69 publications
(74 reference statements)
5
14
4
Order By: Relevance
“…Both in the 1990s and in 2019, Ticino populations were largely dominated by vc types EU‐01, EU‐02 and EU‐05 (and partially EU‐06), which are the most frequent vc types in central Europe (Robin & Heiniger, 2001). A relative stability of vc type diversity over time was also recently reported by Ježić et al (2021) for other C. parasitica populations in Switzerland, Croatia and North Macedonia. These results of retained low vc type diversity in the presence of a deleterious mycovirus are in striking contrast to findings on the invasive forest pathogen Ophiostoma novo ‐ ulmi , the causal agent of Dutch elm disease.…”
Section: Discussionsupporting
confidence: 81%
“…Both in the 1990s and in 2019, Ticino populations were largely dominated by vc types EU‐01, EU‐02 and EU‐05 (and partially EU‐06), which are the most frequent vc types in central Europe (Robin & Heiniger, 2001). A relative stability of vc type diversity over time was also recently reported by Ježić et al (2021) for other C. parasitica populations in Switzerland, Croatia and North Macedonia. These results of retained low vc type diversity in the presence of a deleterious mycovirus are in striking contrast to findings on the invasive forest pathogen Ophiostoma novo ‐ ulmi , the causal agent of Dutch elm disease.…”
Section: Discussionsupporting
confidence: 81%
“…Reduced landscape connectivity between the sites in Croatia is supported by previous studies, which showed a reduced diversity of the fungal host in Kast relative to other Croatian sites ( Ježić et al. 2018 , 2021 ).…”
Section: Discussionsupporting
confidence: 74%
“…Historically, characterizing intra-host virus populations was limited by sequencing capabilities that constrained researchers to host-level virus consensus sequences (often at small amplicons e.g.< 600 base pairs ‘bp’, Kinoti et al. 2017 ; Ježić et al. 2021 ) or a small number of intra-host haplotypes obtained through cloning and Sanger sequencing (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The most remarkable result from our data is the presence of 51 different microsatellite haplotypes of C. parasitica in a geographic region as small as South Tyrol. This diversity is considerably higher than in many other European populations, for example, 57 haplotypes were found collectively in Switzerland, Croatia and Macedonia [33]. In addition, we found three genetic clusters in the region, whereas two different clusters were found in a multinational study; one in Switzerland and Croatia and another in Macedonia [33].…”
Section: Discussioncontrasting
confidence: 60%
“…A close relationship between the genotypes found in South Tyrol and those found in neighboring regions, such as northern Italy and Switzerland, was depicted in the PCoA, which also indicates that the direct introduction of genotypes to South Tyrol from China or Japan is unlikely as both clusters were clearly separated. A recent study also found that most of the central-western European populations of C. parasitica could be related to the first introduction event to Italy in the 1930s [33]. The high VC-type and microsatellite haplotype diversity in the region led us to hypothesize that the neighboring populations may have actively played a role in increasing local genetic diversity through natural dissemination or human-mediated transmission.…”
Section: Discussionmentioning
confidence: 91%